2023
DOI: 10.48550/arxiv.2301.12712
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of solvent on state-to-state population transport in multistate systems using coherences

Abstract: We present an approach of analyzing the transport of a quantum particle in a non-trivially connected extended system interacting with a dissipative medium. There are broadly two different aspects of the problem that affect the route taken by the transport process. First is obviously the couplings between the various sites, which translates into the intrinsic "strength" of a channel. Apart from the inter-site couplings, the solvents affecting the energies of the sites, and their relative coupling strengths and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The usual practice is to focus the numerical studies on the evolution of the population in the excited states of each of the chromophores. Here, we additionally use the recently developed coherencebased analytic techniques [43][44][45][46] to unravel the pathways that the excitation takes and the impact of the vibrational modes. Baker and Habershon [47] have explored these pathways in FMO using the Lindblad master equation.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The usual practice is to focus the numerical studies on the evolution of the population in the excited states of each of the chromophores. Here, we additionally use the recently developed coherencebased analytic techniques [43][44][45][46] to unravel the pathways that the excitation takes and the impact of the vibrational modes. Baker and Habershon [47] have explored these pathways in FMO using the Lindblad master equation.…”
mentioning
confidence: 99%
“…More recently, Dani and Makri have shown that the time-derivative of the on-site populations is related to linear combinations of the off-diagonal terms of the reduced density matrix [44], and visualized the coherences in forms of maps that encode information about the dynamics of the system [45]. We extended these ideas to partition the time-dependent population change on a site in terms of transport along different state-to-state channels, which is useful for understanding the instantaneous population transfer in these systems with complex interconnects [46]. To explore the overall importance of the different pathways using this coherence-based analysis, we use a modified version of the integrated flux approach [43] and define a time-averaged state-to-state population transfer:…”
mentioning
confidence: 99%
See 1 more Smart Citation